Analisis Framing Pemberitaan Pembakaran Al-Qur’an di Media Online - Hakim, Lukman; Hanafi, Alif (UIN Sunan Ampel Surabaya, 2023)
This study aims to analyze the news packaged by online media CNBC Indonesia and NU Online media in conveying the burning of the Koran in Sweden. This research uses Robert N. Entman's framing analysis method with a qualitative approach. The results of the study show that the online media CNBC Indonesia and NU Online media both provide news about the burning of the Koran that occurred in Sweden. The recent burning of the Koran in Sweden has become a concern for many people. Not only for Swedish people. But the world community too. Especially for adherents of Islam. The arson incident disrupted the harmony of inter-religious tolerance in Sweden. Both media also include a chronology of events in every published news. Although not all news is explained in detail regarding the chronology of events and sometimes only briefly included. The online media CNBC Indonesia, in its packaging, is more neutral. Meanwhile, NU Online media tends to show support for Muslims. However, in its delivery, NU Online media continues to insert a message of peace in the news it presents.